Enzymatic depolymerization of alginate by two novel thermostable alginate lyases from Rhodothermus marinus - Dobruchowska, Justyna M.; Bjornsdottir, Bryndis; Fridjonsson, Olafur H.; Altenbuchner, Josef; Watzlawick, Hildegard; Gerwig, Gerrit J.; Dijkhuizen, Lubbert; Kamerling, Johannis P.; Hreggvidsson, Gudmundur O. (Frontiers in Plant Science, 2022)
Alginate (alginic acid) is a linear polysaccharide, wherein (14)-linked -D-mannuronic acid and its C5 epimer, -L-guluronic acid, are arranged in varying sequences. Alginate lyases catalyze the depolymerization of alginate, cleaving the (1→4) glycosidic linkages between the monomers by a β-elimination mechanism, to yield unsaturated 4-deoxy-L-erythro-hex-4-enopyranosyluronic acid (∆) at the non-reducing end of resulting oligosaccharides (α-L-erythro configuration) or, depending on the enzyme, the unsaturated monosaccharide itself. In solution, the released free unsaturated monomer product is further hydrated in a spontaneous (keto-enol tautomerization) process to form two cyclic stereoisomers. In this study, two alginate lyase genes, designated AlyRM3 and AlyRM4, from the marine thermophilic bacterium Rhodothermus marinus (strain MAT378), were cloned and expressed in Escherichia coli. The recombinant enzymes were characterized, and their substrate specificity and product structures determined. AlyRM3 (PL39) and AlyRM4 (PL17) are the most thermostable alginate lyases described to date with temperature optimum of activity at ~75°C and 81°C, respectively. The pH optimum of activity of AlyRM3 is ~5.5 and AlyRM4 at pH 6.5. Detailed NMR analysis of the incubation products demonstrated that AlyRm3 is an endolytic lyase, while AlyRm4, as an exolytic lyase, cleaving monomers from the non-reducing end of oligo/poly-alginates.